The Shah’s China policy: from hostility to rapprochement (a neoclassical realist view) - Ehsan Razani; Nor Azizan Idris (Journal of Faculty of Social Sciences and Humanities. Universiti Kebangsaan Malaysia, 2015)
This paper aims to examine the development of Iran’s China policy under Mohammad Reza Pahlavi during the years between 1949 and 1979. The main theme of this study is based on the question that how, and due to what influences, Iran’s foreign policy towards China evolved under the same leader in the context of the Cold War. Along this line, via adopting a neoclassical realist approach, the present study attempts to explain the Shah’s China policy by taking into account the role of both systemic and domestic variables. As this paper will argue, the structure of the international system and superpower politics have been the primary determinants of Iran’s behavior towards China during the Shah’s reign. However, the Iranian monarch’s perception of the East-West power play, his understanding of China’s position in the international balance of power, and his realistic calculations of the costs and benefits of relations with the PRC have acted as intervening factors that influenced Iran’s China policy at that time.